2022
DOI: 10.3233/jifs-213514
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Human activity recognition based on an amalgamation of CEV & SGM features

Abstract: The method of marking video clips with action symbols is known as vision-based human activity recognition. Robust solutions to this problem have a variety of practical implementations. Due to differences in motion performance, recording environments, and inter-personal differences, the challenge is difficult. We specifically resolve these problems in this study work, and we solve imitations of state-of-the-art research. Projected human activity recognition is based on an amalgamation of CEV & SGM features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…First, we conduct thorough ablation research on KARD to evaluate the efficacy of the dependence feature matrix we have suggested and the fully gated attention. On the dataset (as shown in Table 3), we compare our model to state-of-the-art models [28,30,33], before analyzing how much efficiency gain there is on target datasets. We show that pretraining has a major impact on how effectively our model generalizes.…”
Section: Methods Accuracy (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…First, we conduct thorough ablation research on KARD to evaluate the efficacy of the dependence feature matrix we have suggested and the fully gated attention. On the dataset (as shown in Table 3), we compare our model to state-of-the-art models [28,30,33], before analyzing how much efficiency gain there is on target datasets. We show that pretraining has a major impact on how effectively our model generalizes.…”
Section: Methods Accuracy (%)mentioning
confidence: 99%
“…Instead of taking advantage of fine-tuning action recognition models, previous techniques were only tested on target datasets. Recent research [31][32][33]38,39] proposed view-invariant using 2D or 3D incorporating algorithms with joints performed on our evaluated datasets [25,[31][32][33][34][35]38,39] that do not correspond to legit, and thus these techniques struggle to improve the action recognition performance on regression tasks with practical and mostly used databases [40][41][42][43]. These algorithms were developed to investigate the transferability of action recognition using the human skeleton.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters maximise the probability that is calculated by link prediction algorithms using data that has been actually observed. Several state-of-the-art methods for dimension reduction in feature extraction and selection for feature detection are presented in [24][25][26][27]. For instance, authors [28] established a non-asymptotic risk bound for the maximum likelihood estimator of network connection probabilities.…”
Section: Related Workmentioning
confidence: 99%